2021
DOI: 10.5187/jast.2021.e74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reducing sodium chloride based on the sensory properties of meat products and the improvement strategies employed: a review

Abstract: Upload this completed form to website with submission ARTICLE INFORMATION Fill in information in each box below Article Type Review articleArticle Title (within 20 words without abbreviations) Effect of reducing sodium chloride based on the sensory properties of meat products and the improvement strategies employed: A review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Li et al (2015) reported increases in As expected, the water-activity values decreased with salt content in the emulsions (𝑝 < 0.05) from 0.93 to 0.88, showing that higher salt content affected the concentration of free water. NaCl is a reducer of aw and, therefore, limits microbial growth (Kim et al, 2021). In this sense, the reduction of salt between 40 and 60% in meat emulsions results in greater free water, which could facilitate microbial growth.…”
Section: Physicochemical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al (2015) reported increases in As expected, the water-activity values decreased with salt content in the emulsions (𝑝 < 0.05) from 0.93 to 0.88, showing that higher salt content affected the concentration of free water. NaCl is a reducer of aw and, therefore, limits microbial growth (Kim et al, 2021). In this sense, the reduction of salt between 40 and 60% in meat emulsions results in greater free water, which could facilitate microbial growth.…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…Reducing the salt leads to decreased extraction of myofibrillar proteins, resulting in a less elastic and hard gel matrix in meat emulsion, as Kim et al. (2021) noted. Grasping the rheological traits of the composite gel system throughout the thermal gelation phase is crucial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myofibril protein (MP) is one of the major components in the muscles of various animals, and it plays a substantial role in the physicochemical and textural properties of emulsion systems ( Choi et al, 2011 ). MP is a salt-soluble protein that must be extracted from muscle using sodium chloride or sodium phosphates when manufacturing meat products ( Kim et al, 2021a ). The degree of MP dissolution affects the textural and emulsifying properties of meat products ( Zayas, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium chloride and phosphates were used to prepare a gel matrix of myofibrillar protein for a desirable texture and flavor ( Lee et al, 2010 ; Li et al, 2021 ; Sun et al, 2011 ). However, high sodium levels cause chronic diseases; thus, a proper control of its degree of ingestion can prevent complications and promote human health ( Desmond, 2006 ; Kim et al, 2021a ). Thus, various researchers have developed novel technologies to increase the functional properties of myofibrils to enhance the clearance of sodium phosphates ( Yong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%